Analysis of The Influence of Student Decisions in Using Artificial Intelligence (AI) As a Learning Reference - Anggraini, Feby; Meutia, Sri; Irwansyah, Defi (TALENTA Publisher, 2025)
Education is one of the many facets of human existence that have changed as a result of the advancement of artificial intelligence (AI). The goal of artificial intelligence (AI), a subfield of computer science, is to create computers and systems that can carry out operations that normally call for human intellect. According to data, the number of people using AI is expected to reach 3.33 million annually by 2030. Out of the 100 respondents who received the surveys, 100 said they utilize AI apps. Students in semesters two (19%), four (36%), six (17%), and eight (28%), respectively, make up the distribution of use. 90% of AI is used as a learning reference, compared to 10% for thesis. This study uses the Technology Acceptance Model (TAM) technique as a theoretical framework to ascertain the perceptions that help Industrial Engineering students decide whether to use AI as a learning reference. The analysis's findings indicate that perceived advantages (38.64%), perceived ease of use (40.73%), and actual usage (16.81%) are the perceptions that affect students' decisions in Malikussaleh University's Industrial Engineering department. The development of AI integration tactics in higher education can benefit greatly from these discoveries.